1996
DOI: 10.1002/j.1460-2075.1996.tb00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of DNA-tracking by two sliding-clamp proteins.

Abstract: Bacteriophage T4 gene 45 protein (gp45) and Escherichia coli beta are DNA‐tracking sliding‐clamp proteins that increase processivity by tethering their conjugate DNA polymerases to DNA. gp45 also activates T4 late transcription. DNA loading of gp45 and beta requires ATP or dATP hydrolysis; efficient loading at primer‐template junctions is assisted by single‐stranded DNA‐binding proteins. The kinetics of gp45 loading and tracking have been examined by DNase I footprinting of linear DNA with one blunt end, one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
(57 reference statements)
1
28
1
Order By: Relevance
“…However, this large footprint is likely explained by the ability of the ␥ complex to load multiple clamps onto DNA (4), thereby covering the duplex portion of the primed template with several ␤ rings. Studies such as this in the T4 system have demonstrated that a 660-bp stretch of duplex DNA can be protected from DNase I via packing the entire region with the T4 clamp, gp45 protein (50).…”
Section: Discussionmentioning
confidence: 98%
“…However, this large footprint is likely explained by the ability of the ␥ complex to load multiple clamps onto DNA (4), thereby covering the duplex portion of the primed template with several ␤ rings. Studies such as this in the T4 system have demonstrated that a 660-bp stretch of duplex DNA can be protected from DNase I via packing the entire region with the T4 clamp, gp45 protein (50).…”
Section: Discussionmentioning
confidence: 98%
“…All of these studies blocked the DNA substrate in an irreversible manner, by binding either avidin or an antibody to the DNA ends or by incorporating some type of DNA secondary structure at the DNA ends. The lac repressor-lac operator interaction has been extensively characterized and has been used previously to block various replication proteins from tracking along the DNA (49,52). We took advantage of this system as a means to reversibly block DNA ends during analysis of the interaction of the MSH2-MSH6 and MLH1-PMS1 complexes with DNA immobilized on an IAsys affinity biosensor.…”
Section: The Lac Repressor-lac Operator Interaction Provides a Reversmentioning
confidence: 99%
“…The lac repressor-lac operator system has been used previously in studies of replication proteins tracking along the DNA (49). Here this system was used in conjunction with an IAsys biosensor instrument from Thermo Affinity Sensors, which detects total internal reflectance and allows monitoring of binding and dissociation in real time, in order to develop a system for studying the ability of MMR proteins to move along the DNA.…”
mentioning
confidence: 99%
“…Gp45, the processivity factor of the T4 DNA polymerase, is loaded onto DNA at primer-template junctions by its conjugate clamp loader, the T4 gp44/gp62 complex. Because the DNA-mounted state of gp45 is transient (Fu et al, 1996), a supply of loading sites must be maintained for continual reattachment, which in turn requires continued DNA synthesis. This is the basis of the dependence of active T4 late transcription on concurrent DNA replication in vivo.…”
Section: Introductionmentioning
confidence: 99%